Effects of biochar addition or grass planting on infiltrations into a sandy soil in the Loess Plateau in China - Wu, Lei; Xu, Liujia; Yang, Hang; Ma, Xiaoyi (Earth surface processes and landforms, 2024)
Changing the soil and underlying surface conditions is a key practice for realizing irrigation on‐site storage and infiltration. However, biochar addition and grass planting effects on soil infiltration and water retention capacity remain unclear. The effects of 0% biochar (C1), 1% biochar (C3), 2% biochar (C4), 3% biochar (C5) under ryegrass and 0% biochar (C2), 1% biochar (C6), 2% biochar (C7) and 3% biochar (C8) under Festuca arundinacea on infiltration behaviours were modelled by using sandy loessial soil columns with ‘bare soil + 0% biochar’ as the control (CK). (i) There is a linear relationship between cumulative infiltration and CK–C8 treatment wetting fronts (R2 ≥ 0.982), which showed an initial rising trend and then tended to gradual, and the influence of different treatments was primarily reflected in the middle and late infiltration stages. (ii) Both biochar and grass planting decreased the soil infiltration capacity compared with that of the CK treatment. A high biochar addition rate was beneficial for inhibiting soil water infiltration and improving water retention ability in sandy loessial soil, however, ryegrass soil infiltrabilities under 1%, 2% and 3% biochar were all stronger than that of F. arundinacea. (iii) The cumulative infiltration fitting effects in different treatments with the Kostiakov, Kostiakov–Lewis, Philip, USDA–NRCS, Horton and Green–Ampt equations were all good, although there were some differences in the infiltration rate curves under the six different fitting equations. This study is helpful in understanding effective sandy loessial soil storage ability for irrigation and efficient water resource usage. Effects of 0% biochar (C1), 1% biochar (C3), 2% biochar (C4), 3% biochar (C5) under ryegrass and 0% biochar (C2), 1% biochar (C6), 2% biochar (C7) and 3% biochar (C8) under Festuca arundinacea on sandy loam soil infiltrations were modelled with ‘bare soil + 0% biochar’ as the control (CK).